Nanoporous MoS2 monolayer as a promising membrane for purifying hydrogen and enriching methane. (10th August 2017) - Zhang, Yadong; Meng, Zhaoshun; Shi, Qi; Gao, Haiqi; Liu, Yuzhen; Wang, Yunhui; Rao, Dewei; Deng, Kaiming; Lu, Ruifeng
Abstract: We present a theoretical prediction of a highly efficient membrane for hydrogen purification and natural gas upgrading, i.e. laminar MoS2 material with triangular sulfur-edged nanopores. We calculated from first principles the diffusion barriers of H2 and CO2 across monolayer MoS2 to be, respectively, 0.07 eV and 0.17 eV, which are low enough to warrant their great permeability. The permeance values for H2 and CO2 far exceed the industrially accepted standard. Meanwhile, such a porous MoS2 membrane shows excellent selectivity in terms of H2 /CO, H2 /N2, H2 /CH4, and CO2 /CH4 separation (>10 3, > 10 3, > 10 6, and > 10 4, respectively) at room temperature. We expect that the findings in this work will expedite theoretical or experimental exploration on gas separation membranes based on transition metal dichalcogenides.